The potential of the gut microbiome for identifying Alzheimer’s disease diagnostic biomarkers and future therapies - Zhan, Yu; Al-Nusaif, Murad; Ding, Cong; Zhao, Li; Dong, Chunbo (Frontiers in Neuroscience, 2023)
Being isolated from the peripheral system by the blood-brain barrier, the brain has long been considered a completely impervious tissue. Recent findings show that the gut microbiome (GM) influences gastrointestinal and brain disorders such as Alzheimer’s disease (AD). The pathogenesis of several hypotheses, such as neuroinflammation, tau hyperphosphorylation, amyloid plaques, neurofibrillary tangles, and oxidative stress, has not been fully elucidated to explain the origin and progression of AD. Epigenetic, molecular, and pathological studies suggest that GM influences AD development and have endeavored to find predictive, sensitive, non-invasive, and accurate biomarkers for early disease diagnosis and monitoring of progression. GM involvement in AD is a hot topic; more research is being conducted on the utility of prospective gut biomarkers for clinical and preclinical diagnosis as well as targeted therapy techniques. Here, we discuss the most recent findings on gut changes in AD, gut-based biomarkers, prospective clinical diagnostic uses, and targeted therapy approaches. Furthermore, we addressed herbal components, which could provide a new venue for AD diagnostic and therapy research.